2016
DOI: 10.1080/15685551.2016.1231030
|View full text |Cite
|
Sign up to set email alerts
|

Designing of cardanol based polyol and its curing kinetics with melamine formaldehyde resin

Abstract: Commercially used industrial baking enamels consist of alkyd or polyester resin with melamine formaldehyde. These resins are mainly derived from fossil resources. Considering growing environmental legislation regarding use of petroleum based raw materials, utilization of renewable resources to synthesize various chemistries can be the only obvious option as far as academia and industries are concerns. The present work deals with exploration of one of the natural resources (Cardanol) for polyol synthesis, its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Based on above equation, LOI values above 26 acquire self‐extinguished property. From the Table it was observed that neat epoxy thermosets and particulate bio composites exhibited self‐extinguished property with LOI value greater than 26 . Char yield for D, DC1 was 29.48 and 26.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Based on above equation, LOI values above 26 acquire self‐extinguished property. From the Table it was observed that neat epoxy thermosets and particulate bio composites exhibited self‐extinguished property with LOI value greater than 26 . Char yield for D, DC1 was 29.48 and 26.…”
Section: Resultsmentioning
confidence: 97%
“…1%, 3%, and 5% SiO 2 loaded composite showed least percentage difference of char residue, which concluded that minimal percentage of SiO 2 was sufficient to lead better thermal stability with 31% of char residue than the bio thermosets. This was due to the behavior of SiO 2 loading which act as thermal barrier from the degradation of products during combustion exhibiting higher char residue with enhanced flame retardancy parameter of the system . However, thermal stability factors of bio based polymers can be assessed using the equation, TS=0.490.25em[]Td5+0.60.25em()Tnormald30Td5 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations